2016
DOI: 10.1074/mcp.m115.055780
|View full text |Cite
|
Sign up to set email alerts
|

Sampling From the Proteome to the Human Leukocyte Antigen-DR (HLA-DR) Ligandome Proceeds Via High Specificity

Abstract: Comprehensive analysis of the complex nature of the Human Leukocyte Antigen (HLA) class II ligandome is of utmost importance to understand the basis for CD4+ T cell mediated immunity and tolerance. Here, we implemented important improvements in the analysis of the repertoire of HLA-DR-presented peptides, using hybrid mass spectrometry-based peptide fragmentation techniques on a ligandome sample isolated from matured human monocyte-derived dendritic cells (DC). The reported data set constitutes nearly 14 thousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 73 publications
10
84
1
Order By: Relevance
“…In light of recent findings, implementation of multiple fragmentation strategies may help overcome this problem in future studies. 53 Nevertheless, for both HLA class I and II we identified several tumor-associated enriched pathways conserved in malignant tissue samples. This shows for the first time that key proteins of intra-and extra-cellular biological processes of carcinogenesis are reflected in HLA ligands and can be used for targeting carcinomas in a more functional manner.…”
Section: Discussionmentioning
confidence: 99%
“…In light of recent findings, implementation of multiple fragmentation strategies may help overcome this problem in future studies. 53 Nevertheless, for both HLA class I and II we identified several tumor-associated enriched pathways conserved in malignant tissue samples. This shows for the first time that key proteins of intra-and extra-cellular biological processes of carcinogenesis are reflected in HLA ligands and can be used for targeting carcinomas in a more functional manner.…”
Section: Discussionmentioning
confidence: 99%
“…We earlier showed that EThcD is especially suited for the characterization of the peptidomes bound to HLA-I (10) and HLA-II molecules (11) and their PTMs (12). Using this workflow, we were able to generate a resource of over 260 phosphorylated HLA-I ligands.…”
mentioning
confidence: 99%
“…From the repertoire of thousands detected MHC II peptides, specific binding motifs can be identified, similar as was shown for class I. 66,76,80 As current tools for MHC II peptide binding predictions are relatively inaccurate, predictions based on these motifs may improve identification of patient-specific, mutation containing MHC II ligands (Fig. 3C).…”
mentioning
confidence: 99%
“…Stringent control over false discovery rate (FDR) and peptide spectrum match (PSM) scoring ensures accurate and reliable results; typically one to five percent FDR thresholds are applied to peptidomic datasets using the target-decoy approach. 80,81 Inclusion of exhaustive lists of known mutations from repositories like the TCGA or COSMIC will increase the level of false positives and therefore better-personalized reference databases should be used. To quantify mutation containing HLA ligands, the sample can be spiked with synthetic peptides labeled with stable heavy isotopes (Fig.…”
mentioning
confidence: 99%